INDUCED RADIO AND X-RAY EMISSION FROM AN ACCRETION DISK - Prigara, F. V. (Одеські астрономічні публікації, 2017)
Radio and X-ray emission from compact sources with accretion disks (active galactic nuclei, pulsars and X-ray binaries) is considered. It is shown that both radio and X-ray emission from these sources can be interpreted as emission of a hot (T >= 3 x 10^7 K) plasma in the inner part of an accretion disk or in the disk corona. Radio emission is produced by the maser amplification of thermal radio emission in a hot plasma and corresponds to the transitions between highly located energy levels (somewhat similarly to the recombination lines). The X-ray emission is either thermal radiation from dense filaments or is produced by the coherent inverse Compton scattering of radio photons in the same dense filaments. The same mechanism, which gives rise to the maser amplification at radio wavelengths, produces also laser amplification in optical in X-ray binaries.